An Academic Response to Basel 3.5 - Paul Embrechts; Giovanni Puccetti; Ludger Rüschendorf; Ruodu Wang; Antonela Beleraj (Risks, 2014)
Recent crises in the financial industry have shown weaknesses in the modeling of Risk-Weighted Assets (RWAs). Relatively minor model changes may lead to substantial changes in the RWA numbers. Similar problems are encountered in the Value-at-Risk (VaR)-aggregation of risks. In this article, we highlight some of the underlying issues, both methodologically, as well as through examples. In particular, we frame this discussion in the context of two recent regulatory documents we refer to as Basel 3.5.